Uncontrolled Single-Phase Half-Wave Rectifier with a DC Motor - Dwi Rizky Anto (Journal of Marine Electrical and Electronic Technology, 2024)
Uncontrolled Rectifiers are circuits that convert alternating current (AC) voltage sources into direct current (DC) voltage sources. These rectifiers operate without external control or adjustment. Typically, they utilize a single diode, and when only one diode is used, a half-wave rectification is produced. In a single-phase uncontrolled rectifier circuit connected to a DC motor load, the output voltage and current amplitude depend significantly on the motor's applied torque. The higher the motor's torque, the higher the speed achieved; similarly, the higher the applied voltage, the greater the current and speed of the motor. In the context of engineering applications, understanding the dynamics of uncontrolled single-phase half-wave rectifiers is essential for optimizing motor control systems, particularly where cost-effective solutions are required. While such rectifiers are simple in design, their efficiency and impact on motor performance, such as speed regulation and energy consumption, require thorough investigation. Furthermore, exploring the relationship between the torque applied to the motor and the resulting electrical parameters can provide valuable insights for applications in low-power motors, renewable energy systems, or devices where simplicity and efficiency are prioritized over advanced control mechanisms.